THE INFLUENCE OF ASYNCHRONOUS BLENDED PROBLEM-BASED LEARNING ON RETENTION AND LEARNING MOTIVATION OF MIDWIFERY STUDENTS - Purwandyarti Apriliani; Ike Rostikawati Husen; Dani Hilmanto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: According to 21st century priorities in the Global Strategy On Human Resources For Health: Workforce 2030, the abilities of medical practices must be appropiate with the demands of the society. To realize the abilities of medical practices which are apropriate with the demands of the society, are using learning methods that encourage a more active learning process, thereby encouraging the activation of long term memory through the introduction of realistic and contextual cases that can increase the cognitive retention of students. Problem based learning method (PBL) has several limitations. One of them is the high demand of educators in number. Asynchronous blended problem based learning method (ABLE-PBL) is an instructional innovation that may be used in midwifery school institutions that have limited number of educators but they want to optimize the learning process and produce quality graduates who are competent in accordance with the demands of the society. The aim of this study is to know the influence of ABLE-PBL and PBL method on cognitive retention and student learning motivation.Method: This study conducted using a quantitative approach with total sample 37 Universitas Padjadjaran Midwifery students who are fulfilling the inclusion and exclusion criteria, from March to June 2018 by cross over method.Results: This study showed that there was no difference between retention score 1 and retention score 2 of intervention group (ABLE-PBL) and control group (PBL) by using mann-whitney test (p > 0,05), ABLE-PBL and PBL had no difference in affecting cognitive retention and motivation by using chi square test (p > 0.05).Conclusion: ABLE-PBL method and PBL method has no difference in affecting cognitive retention and student learning motivation.